Are busy boards detrimental? - Field, Laura; Lowry, Michelle; Mkrtchyan, Anahit (Journal of Financial Economics, 2013)
Busy directors have been widely criticized as being ineffective. However, we hypothesize that busy directors offer advantages for many firms. While busy directors may be less effective monitors, their experience and contacts arguably make them excellent advisors. Among IPO firms, which have minimal experience with public markets and likely rely heavily on their directors for advising, we find busy boards to be common and to contribute positively to firm value. Moreover, these positive effects of busy boards extend to all but the most established firms. Benefits are lowest among Forbes 500 firms, which likely require more monitoring than advising.